2024
DOI: 10.3847/1538-4357/ad2345
|View full text |Cite
|
Sign up to set email alerts
|

Little Red Dots: An Abundant Population of Faint Active Galactic Nuclei at z ∼ 5 Revealed by the EIGER and FRESCO JWST Surveys

Jorryt Matthee,
Rohan P. Naidu,
Gabriel Brammer
et al.

Abstract: Characterizing the prevalence and properties of faint active galactic nuclei (AGNs) in the early Universe is key for understanding the formation of supermassive black holes (SMBHs) and determining their role in cosmic reionization. We perform a spectroscopic search for broad Hα emitters at z ≈ 4–6 using deep JWST/NIRCam imaging and wide field slitless spectroscopy from the EIGER and FRESCO surveys. We identify 20 Hα lines at z = 4.2–5.5 that have broad components with line widths from ∼1200–3700 km s−1, contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
47
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 162 publications
(257 reference statements)
13
47
1
Order By: Relevance
“…The BH masses for those JWST-detected faint AGNs are M • ∼ 10 6−8 M e , which is 1-2 orders of magnitude lower than those of previously known quasars at z > 4. Intriguingly, some of the sources have extremely red colors in the rest-frame optical bands, while the rest-frame UV color seems fairly consistent with those of known Lyman-break galaxies at similar redshifts (e.g., Harikane et al 2023;Kocevski et al 2023;Labbe et al 2023;Barro et al 2024;Greene et al 2024;Matthee et al 2024). The so-called "little red dot" sources are interpreted to be in a transition stage from a dust-obscured starburst to an unobscured luminous quasar due to the expelling of gas and dust (Fujimoto et al 2022).…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…The BH masses for those JWST-detected faint AGNs are M • ∼ 10 6−8 M e , which is 1-2 orders of magnitude lower than those of previously known quasars at z > 4. Intriguingly, some of the sources have extremely red colors in the rest-frame optical bands, while the rest-frame UV color seems fairly consistent with those of known Lyman-break galaxies at similar redshifts (e.g., Harikane et al 2023;Kocevski et al 2023;Labbe et al 2023;Barro et al 2024;Greene et al 2024;Matthee et al 2024). The so-called "little red dot" sources are interpreted to be in a transition stage from a dust-obscured starburst to an unobscured luminous quasar due to the expelling of gas and dust (Fujimoto et al 2022).…”
Section: Introductionsupporting
confidence: 59%
“…2. An intriguing subset consists of the dust-reddened AGNs (referred to as "little red dots"), characterized by moderate obscuration in the SED and compact morphology (Harikane et al 2023;Kocevski et al 2023;Labbe et al 2023;Barro et al 2024;Matthee et al 2024). This class of AGNs shows a distinctive spectral shape, which can be attributed to a dust-reddened AGN continuum coupled with excess emission in the rest-frame UV produced either by the unobscured stellar continuum of the host galaxy or scattered light from the buried AGN (e.g., Zakamska et al 2005;Polletta et al 2006;Noboriguchi et al 2023).…”
Section: Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its extremely high IR sensitivity has revealed a weak broad component in Balmer emission lines of many high-z galaxies, signaling the presence of low-luminosity active galactic nuclei (AGNs) out to z ∼ 11 (e.g., Greene et al 2024;Maiolino et al 2023). The number density of such AGNs exceeds the extrapolation of the classical QLF by several orders of magnitude (e.g., Harikane et al 2023;Matthee et al 2024), changing the paradigm of SMBH activity happening in the EoR.…”
Section: Introductionmentioning
confidence: 99%
“…Chardin et al (2015Chardin et al ( , 2017 showed that the strong fluctuations in the ionizing background would be a natural consequence of a bright and rare source population, i.e., luminous quasars (see also Meiksin 2020), but the initial suggestions of an overabundant faint quasar population at z > 5 (Giallongo et al 2015) are now generally disfavored (e.g., D' Aloisio et al 2017;Matsuoka et al 2018;Parsa et al 2018). While interest in such quasar-dominated models has begun to resurface in light of the discovery of a substantial population of faint AGNs at z > 5 by JWST surveys (e.g., Harikane et al 2023;Kocevski et al 2023;Labbe et al 2023;Maiolino et al 2023;Matthee et al 2024), due to their typically highly reddened nature, it is still unknown whether these objects contribute substantially to the ionizing photon budget. explored the possibility that galaxysourced ionizing background fluctuations could be amplified by a coupling to the mean free path of ionizing photons (see also D'Aloisio et al 2018) following analytic arguments from McQuinn et al (2011), but in order to match the broad distribution of Lyα forest opacity, the average mean free path would have to be a factor of a few shorter than the extrapolation from lower-redshift measurements (Worseck et al 2014).…”
Section: Introductionmentioning
confidence: 99%